Indigenous knowledge preservation as a sign of respect for culture: concerns of libraries, archives and museums - Adetoun A. Oyelude (Insights: The UKSG Journal, 2023)
Indigenous or traditional knowledge (IK) holders face a lack of respect and appreciation for such knowledge. Respect for culture means following protocols, accepting diversity and recognizing indigenous cultures as living and continuously evolving. This is a ‘hot topic’, and the central goal of this article is to advance understandings to allow cultural memory institutions (libraries, archives and museums) to respect, affirm and recognize indigenous ownership of their traditional and living indigenous knowledges and to respect the protocols for their use. The various ways of managing and preserving indigenous knowledge, especially using new technologies in the digital era, will be explored and ideas on how to respect the indigenous culture, even in the process of documenting or preserving in academic libraries, will be outlined. Libraries involved in IK preservation will be encouraged to develop protocols by collaborating with each other and engaging the community, to preserve each unique culture in a respectful manner. Intellectual property rights of knowledge holders, respect for these rights and procedures to adopt will be described. Activities undertaken to preserve indigenous knowledge are assessed and suggestions made on how library and information science professionals could more efficiently handle indigenous knowledge preservation as respect for culture.